2020
DOI: 10.1177/2397791420911811
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of hexagonal boron nitride nanoparticles as an additive in the lubricating oil and studying its application

Abstract: Lubricating oil plays an important role in minimizing the friction and wear of many mechanical systems. The additives present in the conventional lubricant are inadequate to reduce the friction and wear of today’s mechanical systems. However, the use of these additives has a significant effect on the environment due to their fast chemical degradation. In recent years, nanoparticle-based lubricant has attracted great attention due to their friction reduction behavior. Therefore, it is of great importance to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…In a previous work, 40 we have carried out tribological analyses of engine components using hBN‐based nanofluid by employing a realistic diesel engine. The results showed that the friction and wear of engine components were minimized due to the mending/patching effects of nanoparticles in the base oil which resulted in the formation of tribolayer.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, 40 we have carried out tribological analyses of engine components using hBN‐based nanofluid by employing a realistic diesel engine. The results showed that the friction and wear of engine components were minimized due to the mending/patching effects of nanoparticles in the base oil which resulted in the formation of tribolayer.…”
Section: Introductionmentioning
confidence: 99%
“…This contains 25% PET in sand replacement + nanoadditive and although its cost is high, it generated the best results in both compression and absorption. However, it could also be considered the dosage with 25% PET in replacement of sand without nanoadditive, as its results are acceptable, and the cost is lower [49]- [55].…”
Section: Resultsmentioning
confidence: 99%
“…Potential aerosol generating procedures using HBN nanomaterials include use as lubricants for functions including mechanical lubrication and the coating of bullets. [54][55][56] The SNOT colloidal suspensions were either vortexed or sonicated under varying conditions (Figure 1A, Table 2) with intermittent rest periods of 1 minute to create test suspensions. 57 Then suspensions containing SNOT and HBN were sonicated in probe and cup sonicators at various time points and intensities, and the diameter of the resulting colloidal solutions was analyzed with DLS [Figure 1B, Table 3).…”
Section: Optimization Of Sonication Procedures To Disperse Nanomateri...mentioning
confidence: 99%